PENERAPAN TEKNOLOGI AUGMENTED REALITY PADA MEDIA PEMBELAJARAN - Ossy Dwi Endah Wulansari; T M Zaini; Bobby Bahri (IIB Darmajaya, 2013)
Application of the Technology of Augmented Reality is projected as a learning process of learning media innovation with conventional methods (slides) and using guidebooks and the like can be used to support the learning process itself in order to give understanding to users about the material presented. In contrast to conventional learning, applied technology is interactive and more interest because the information is delivered more interactive with the user use. The utilization of computer graphics Applications allow illustrate images together in the form of animation (moving images and three-dimensional) that can explored in different angles (top, bottom, right, left) so it will give you a better understanding of the user. The application of computer application was developed using one of the methods of software development which is